PEDAGOGICAL-PSYCHOLOGICAL CHARACTERISTICS OF DEVELOPING NECESSARY PROFESSIONAL TRAITS IN FUTURE PHYSICAL EDUCATION TEACHERS - Abdullayev Rustam Abduvaliyevich (International Scientific and Current Research Conferences, 2024)
In this article, particular emphasis is placed on G. Allport’s theory of functional autonomy of motives, which occupies a prominent position among foreign researchers in the field of motivation. In the presented theory, the transformation and systematic development of motives are interpreted as a process. In his conceptual framework, G. Allport extensively utilizes the ideas of general systems theory, especially the concept of open systems.